Isolation and Identification of Ethanol and Glucose Tolerance Yeasts Strain from Tacca leontopetaloides (Microbiology Indonesia, 2017)
The research aimed to isolate and characterize indigenous yeast strain from Tacca leontopetaloides with respect to the ethanol and glucose tolerance ability. Research done experimentally and the data analyzed descriptively. Yeasts isolated from 1g Tacca leontopetaloides grown at modified Potato Dextrose Agar/PDA (Oxoid Ltd.) with 3% Yeasts Extract/YE (Kraft Foods) and 10 ppm amoxicillin addition. Yeasts-like colony was tested in the ability to tolerate ethanol and glucose contents by grown on modified Nutrient Broth/NB (Oxoid Ltd.) with 3% Yeasts Extract/YE (Kraft Foods) and 10 ppm amoxicillin then added with glucose monohydrate (10%, 20%, 30%) or ethanol (10%, 20%, 30%) and incubated for 72h at ambient (23-28°C). Optical density (OD) was read for UV absorbance at 600 nm using UV-Vis spectrophotometer every 24h until 72h. The strain of best isolate with the ability to tolerate high ethanol and glucose contents were identified by the sequence analysis of ITS (Internal Transcribed Spacer) region using primers ITS1 (5′-TCCGTAGGTGAACCTGCGG-3′) and ITS4 (5′-TCCTCCGCTTATTGATATGC-3′). The sequencing was performed at Macrogen Inc. (Seoul, South Korea), and the sequences was compared with the GenBank database using BLAST (Basic Local Alignment Search Tools) algorithm (http//:www.ncbi.nlm.nih.gov/BLAST/). Results shown there are four yeasts-like isolate and the TK1 isolate showed the best ethanol tolerance ability with highest OD at 30% ethanol concentration (0.486) and the highest OD at 30% glucose concentration (1.732). The species identification identified the TK1 isolate as 99% identical with Candida natalensis (ITS1) and 100% identical with Candida quercitrusa (ITS4).